The cultural politics of emotion - Ahmed, Sara (Edinburgh University Press, 2014)
This is a bold take on the crucial role of emotion in politics. Emotions work to define who we are as well as shape what we do and this is no more powerfully at play than in the world of politics. Ahmed considers how emotions keep us invested in relationships of power, and also shows how this use of emotion could be crucial to feminist and queer political movements. Debates on international terrorism, asylum and migration, as well as reconciliation and reparation are explored through topical case studies. In this textbook the difficult issues are confronted head on. New for this edition: a substantial 15,000-word Afterword on 'Emotions and Their Objects' which provides an original contribution to the burgeoning field of affect studies; a revised Bibliography; and updated throughout.
Keywords: approches et analyses; capitalisme; corps; discipline; féminisme; histoire et politique; militance; philosophie; queer; ressource en ligne; sciences humaines; systèmes d'oppressions; thématiques; émotions; études culturelles

Où en sommes-nous avec le féminisme en art? - Lamoureux, Ève; St-Gelais, Thérèse (Recherches féministes, 2014)
Keywords: amériques; approches et analyses; corps; cours; discipline; fem1000; har4600; histoire de l'art; pratiques féministes; premier cycle; queer; québec; ressource en ligne; régions géographiques; thématiques

The Black body in ecstasy: reading race, reading pornography - Nash, Jennifer C. (Next wave : new directions in women's studies, 2014)
In The Black Body in Ecstasy, Jennifer C. Nash rewrites black feminism's theory of representation. Her analysis moves beyond black feminism's preoccupation with injury and recovery to consider how racial fictions can create a space of agency and even pleasure for black female subjects. Nash's innovative readings of hardcore pornographic films from the 1970s and 1980s develop a new method of analyzing racialized pornography that focuses on black women's pleasures in blackness: delights in toying with and subverting blackness, moments of racialized excitement, deliberate enactments of hyperbolic blackness, and humorous performances of blackness that poke fun at the fantastical project of race. Drawing on feminist and queer theory, critical race theory, and media studies, Nash creates a new black feminist interpretative practice, one attentive to the messy contradictions—between delight and discomfort, between desire and degradation—at the heart of black pleasures.
Keywords: 1900-1999; 1970-1979; 1980-1989; afro-féminisme; amériques; approches et analyses; cinéma; communication; corps; cours; discipline; féminisme afroaméricain; féminisme pop; lit4700; pornographie; premier cycle; périodes historiques; queer; régions géographiques; sexualité; thématiques; états-unis; études culturelles